The Influence Of Social Interaction On Tiktok Shop Purchasing Decisions - Sumantyo, Franciscus Dwikotjo Sri; Hussaen, Saddam; Setyawan, Aditya Chandra; Hamdiah, Hamdiah; Yakin, Rahmat Aji Nur (PT. Sharia Journal and Education Center, 2026)
This study aims to analyze the influence of social interaction on purchasing decisions on the TikTok Shop platform. In the era of social commerce, the shift from transactional to interactional shopping experiences has redefined consumer behavior. Through the lens of Social Cognitive Theory and the concept of